Reviews (Blackfriars, 1923)
Book Reviews in this Article The Philosophy of Art, being‘Art et Scolastique,’by Jacques Maritain, translated by the Rev. John O'Connor, S.T.P., with an introduction by Eric Gill, O.S.D. St. Dominic's Press, Ditchling, Sussex. The First Red Cross. The Inquisition. By Hoffman Nickerson. With a preface by Hilaire Belloc. Oriental Blossoms, by Gwendoline Goodwin. Sonnets and Other Verses. By A. W. Fancies Versus Fads, by G. K. Chesterton.